KONFLIK KEPENTINGAN DALAM PENGELOLAAN MASJID BESAR KAUMAN YOGYAKARTA - Muhammad Chawari (BRIN, 2005)
With the large number of visitors that are almost evenly distributed every month of the year, of course, it will invite the people around the Kauman Grand Mosque to be able to take advantage of this opportunity, namely in the form of services. Activities in the form of services carried out by residents of the surrounding community, in a sense, will certainly